A case of central odontogenic fibroma in a pediatric patient: Mandibular reconstruction with parietal bone. Issue 3 (May 2015) - Shiraishi, Takeshi; Uehara, Masataka; Fujita, Shuichi; Ikeda, Tohru; Asahina, Izumi
Abstract Central odontogenic fibromas (COFs) are benign odontogenic tumors derived from the dental mesenchymal tissues. They are rare tumors that account for 0.1–12.8% of all odontogenic tumors [1–8]. The location of COFs and the tumor incidence with respect to sex and age distributions are not well understood. Clinical features of the tumor include an asymptomatic expansion of the cortical plate of the mandible or maxilla and unilocular or multilocular radiolucency. Here, we describe a case of COF in the posterior region of the left mandible in a 3-year-old girl. The mandible was segmentally resected with the tumor and reconstructed with a parietal bone graft. No signs of recurrence or postoperative complications including occlusion were found. The esthetic outcome was satisfactory.